Nine receptors and binding proteins, four drugs, and one woman: Historical and personal perspectives - Novick, Daniela (Frontiers in Drug Discovery, 2022)
In the era of bioinformatics and high throughput techniques, it is quite tempting to forget the advantage of an old yet efficient and straightforward technique, the ligand-affinity-chromatography, in the search for unknown proteins. This type of separation is based on an interaction between the target analyte and a ligand coupled covalently to a resin. Thousands fold purification is achieved in one step, which is crucial when an extremely rich sources of naturally occurring proteins such as human urine or plasma are used. Prior to the completion of the genome project this method facilitated rapid and reliable cloning of the corresponding gene on the basis of the isolated protein partial amino acid sequence. Upon completion of this project, a partial protein sequence was enough for retrieving its complete mRNA and hence its complete protein sequence. Ligand-affinity-chromatography is indispensable for the isolation of both expected and unexpected binding proteins some found by serendipity. Having the tools, my approach of combining a rich source of human proteins (1000-fold concentrated human urine) with this highly specific isolation method yielded proteins from both groups. The expected proteins included the two receptors for TNF (TBPI and TBPII), the Type I and Type II interferon receptors (IFN/R, IFN-R), and the receptors for IL-6 and LDL. The unexpected group of proteins include the IL-18 Binding Protein (IL-18BP), the IL-32 binding protein (Proteinase 3), and the Resistin that binds Heparanase. The discovery of Type I IFN receptor was a moment of “eureka” since it put an end to 35 years of worldwide search for this receptor. Using chemical purification methods the TBPII might have never been discovered. Years later it was the TBPII that translated into a blockbuster drug named Enbrel® to treat mainly Rheumatoid Arthritis. IFN-beta translated into the blockbuster drug Rebif® to treat the autoimmune disease Multiple Sclerosis. The IL-18BP translated into the drug Tadekinig alfaTM and is in phase III clinical study for inflammatory and autoimmune pathologies. It saved the life of children born with mutations (NLRC4, XIAP) and is an example of personalized medicine. Covid 19 and CAR-T cytokine storms are recent targets of IL-18BP.